Output-Based Aid in Education : A Solution for Quality Education - Murariu, Inga; Johannes, Lars (World Bank, Washington, DC, 2012)
A number of approaches have been tried to improve school attendance and educational attainment, including the use of Output-Based Aid (OBA). The challenge of introducing OBA in education has often been finding an appropriate definition of 'output' that balances achievement of results with reasonable transfer of performance risk. This review examines several OBA projects in education and describes how they compare to other results-based schemes. It also discusses where the OBA approach fits in the larger spectrum of results-based mechanisms in education, and why it can be successful.